Casertano, G. Os Pré-Socráticos. Trad. de Maria da Graça Gomes de Pina. Col. “Sabedoria Antiga”. São Paulo: Loyola, 2011. - Peixoto, Miriam C. D. (Revista Archai, 2011)
Casertano, G. Os Pré-Socráticos. Trad. de Maria da Graça Gomes de Pina. Col. “Sabedoria Antiga”. São Paulo: Loyola, 2011.